2022
DOI: 10.3390/nu14112258
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence and Correlates of Overweight, Obesity and Physical Activity in Italian Children and Adolescents from Lombardy, Italy

Abstract: Investigating pediatric overweight and physical activity correlates is essential to design effective preventive programs. We used regional data (Lombardy, northern Italy) from the 2019 survey “OKKio alla Salute” (3093 children aged 8–9 years with measured anthropometric data), and from the 2018 wave of the “Health Behaviour in School-aged Children” survey (2916 adolescents aged 11–15 years with self-reported anthropometric data). In both the surveys, a cluster sampling methodology was used. Unconditional multi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
1
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 50 publications
(57 reference statements)
0
1
0
Order By: Relevance
“…Another finding of our study was that the effects of screen time varied by age. This aligns with previous research that has indicated a significant association between recreational screen time, particularly TV viewing, and weight status among adolescents but not children [43,44]. Jakubec et al suggest that this variation could be explained by a decline in family influence on health behaviors during the developmental shift from childhood to adolescence, whereby adolescents are less restricted by parents and more prone to unhealthy weight gain due to excessive screen use [45].…”
Section: Discussionsupporting
confidence: 85%
“…Another finding of our study was that the effects of screen time varied by age. This aligns with previous research that has indicated a significant association between recreational screen time, particularly TV viewing, and weight status among adolescents but not children [43,44]. Jakubec et al suggest that this variation could be explained by a decline in family influence on health behaviors during the developmental shift from childhood to adolescence, whereby adolescents are less restricted by parents and more prone to unhealthy weight gain due to excessive screen use [45].…”
Section: Discussionsupporting
confidence: 85%
“…In sports contexts, females and males are not encouraged in the same way due to sex-stereotyped beliefs [40]. This appears in sex disparities in sports participation: in Italy, scant physical activity was higher among females and older adolescents [41]. Morano et al [40] reported that 41% of girls and 59% of boys 11-19 years old practice sports.…”
Section: Introductionmentioning
confidence: 99%
“…It was estimated by the World Obesity Federation that there would be 206 million obese children/adolescents in 2025, and 254 million in 2030 [2]. Out of 43 European countries, Italy ranks as the 11th among overweight/obesity children aged 13 years and 20th among subjects aged 15 years [3]. In the pediatric age, gender-specific body mass index (BMI)-for-age percentile curves are usually used for the diagnosis of both overweight and obesity.…”
Section: Introductionmentioning
confidence: 99%